A Review of Fruit and Vegetable Food Safety in Tanzania - Wanyama, R.; Ernest, Z.; Mvungi, H. (International Food Policy Research Institute, 2022)
This technical report produced by FRESH Initiative Partner Applied Horticultural Research, in collaboration with FRESH Initiative Partner World Vegetable Center, provides an overview of the literature on the production practices affecting quality and safety of vegetables and fruits, as well as the evidence of documented health effects of fresh produce contamination in Tanzania. The report summarizes evidence gaps and provides recommendations for improving food safety practices.